“BEM” An Android Application Model to Enhance Midwifery Students English Speaking Competence - David Sulistiawan Aditya (Journal of Foreign Language Teaching and Learning, 2019)
The lack of exposure and practice in learning English due to the short meeting hours is the main factor contributing to the low level of midwifery students’ English-speaking competence in Indonesia. Mobile-Assisted Language Learning can be one of the ways to cope with this problem. A plethora of learning speaking applications is available in the App Store and Play Store. However, midwifery students need more specific English to meet their needs. This study aims at developing a model of android application to enhance the speaking competence of midwifery students and anchors in the instructional design model. The design was in the five stages, namely: Analyze, Design, Develop, Implement, and Evaluate. Twenty-one midwifery students and two experts of material development and information technology were participants for product implementation and evaluation. The researchers obtained the necessary data through observations, questionnaires, and interviews. The finding of this study was that an android application model named BEM (Basic English for Midwives) developed in this study could enhance the midwifery students speaking competence.